Mengembangkan kepercayaan diri / Ros Taylor; penerjemah, Marina Sofyan; editor, Niken Hananti, Daniel P. Purba - TAYLOR, Ros ; MARINA SOFYAN ; NIKEN HANANTI ; PURBA, Daniel P. (Esensi, 2009)
118 halaman : ilustrasi, foto berwarna ; 19 cm